Synthesis, Characterization, and Biological Applications of Tetramethylpiperidinyl Triazolopyridazine Derivatives - Keesara, Srinivasa Reddy; Bolla, Ratnasekhar; Bharathkumar, Hanumantharayappa; Andugulapati, Sai Balaji; Gundekari, Sreedhar; Varkolu, Mohan (Synlett, 2024)
We have synthesized a series of tetramethylpiperidinyl triazolopyridazine derivatives and screened the molecules for their biological activity against a cancer (NCI-H460) cell line. Among the tested molecules, 2-[3-(2,2,6,6-tetramethylpiperidin-4-yl)-3H-[1,2,3]triazolo[4,5-c]pyridazin-6-yl]-5-(2H-1,2,3-triazol-2-yl)phenol significantly inhibited cell growth with an IC50 value of 5.2 μM. We hope that this study will help in the development of better candidates for the treatment of lung cancer.
Keywords: triazolopyridazines; lung cancer; medicinal chemistry; biological activity; anticancer drugs